Nurturing spirituality among private university lecturers for a higher quality service performance - Saad, Mazni; Ahmad Shah, Norliana; Mohamad Mohan, Noor Malinda; Poniran, Halimi (Arshad Ayub Graduate Business School, 2018)
In today’s teaching environment, the professional lecturer faces many new challenges – from teaching, facilitating, doing administrative work to researching and serving in community services. They need to keep abreast of new changes in education technology and social needs to compete for students. Often lack of subject expertise means a higher timetable load and a lot more new responsibilities that may contribute to a high level of stress and burn-out particularly among new lecturers in private universities. However, information on a lecturer’s coping ability, specifically referred to as spiritual intelligence (SQ) is limited and not yet understood. Thus, this study would like to investigate SQ and how it impacts performance by measuring quality services. The questionnaire survey is on a six-point Likert scale, with data collected from 127 lecturers of 20 private-owned universities located in Selangor, Malaysia. The results show that the SQ level among the young lecturers was quite high. The five sub-dimensions of SQ were found positive and significantly affected the lecturers’ performance. The standardized coefficients beta values indicate that the sub-dimensions of Transcendence and Meaning contributed to 37% and 31% Service Quality respectively. The study suggests that the universities must learn more about the lecturer’s SQ development and how to retain the lecturer’s SQ as they play the prime role of servicing an institution’s most important stakeholder – the students.